A diamagnetically levitated vibration energy harvester for scavaging the horizontal vibration. (9th November 2018) - Ding, Jianqiao; Gao, Jianshe; Su, Yufeng; Zhang, Kun; Duan, Zhiyong
Abstract: The use of vibration energy harvesters for supplying energy to wireless sensor nodes is becoming increasingly popular. In this paper an electromagnetic vibration type energy harvester based on the diamagnetic levitation system is designed, fabricated and tested. The system mainly consists of two pyrolytic graphite sheets, two permanent magnets two inductive coils. The device has been modeled using analytic equations to analyze the motion characteristics and induced voltage by MATLAB. The magnetic field intensity is simulated by FEA software COMSOL Multiphysics 5.2. Theoretical modeling and analyses are carried out to compare with experimental data utilizing the same vibration setup. Throughout the experimental results, the maximal RMS voltage is up to 70.85 mV and the output power can reach 46.5 μ W at 4.6 Hz under horizontal excitation. Both theoretical and experimental results show that this energy harvester can capture low-frequency broadband vibration energy.